Targeting the CCL28-STAT3-PLAC8 axis to suppress metastasis and remodel tumor microenvironment in colorectal cancer - Yang, Yao; Jiang, Qixin; Zhu, Zhe; Zhang, Shun; Du, Tao; Song, Shuzheng; Jiang, Xiaohua (Frontiers in Immunology, 2025)
BackgroundChronic inflammation plays a critical role in the initiation and progression of colorectal cancer (CRC), establishing a close link between the inflammatory microenvironment with tumor invasion and metastasis. However, the regulatory mechanisms by which inflammation-related factors promote CRC progression remain largely unclear.MethodsThe biological significance of PLAC8 in colorectal cancer was investigated through clinical data analysis, mouse models of colitis-associated colorectal cancer, gene knockdown and overexpression, as well as cell migration and invasion assays. Additionally, bioinformatics analysis, activation and inhibition of PI3K/Akt and JAK/STAT3 signaling pathways, along with techniques including CUT&Tag, Western blotting, and qPCR, were employed to comprehensively analyze the detailed molecular mechanisms of PLAC8.ResultsAnalysis of PLAC8 expression in 78 paired clinical samples revealed significantly elevated PLAC8 expression in CRC and was identified as an independent prognostic factor. Increased expression of PLAC8 was further validated in the mouse inflammation-cancer transition model. Genetic manipulation of PLAC8 through overexpression and knockdown unequivocally established its prometastatic function in CRC, with no significant effects on proliferation, oxaliplatin resistance, or colony formation. Pharmacological modulation of AKT signaling using specific activators (SC79) and inhibitors (Capivasertib) confirmed that PLAC8 drives EMT through AKT pathway activation, resulting in increased expression of EMT-related proteins, such as N-cadherin and Snail, thereby enhancing cell migration and invasion. Further correlation analysis, CUT&Tag, and STAT3 inhibition studies revealed that CCL28 activated the STAT3 signaling pathway, promoting PLAC8 expression, and ultimately enhancing CRC invasion and metastasis.ConclusionCCL28-mediated promotion of PLAC8 via the JAK/STAT3 signaling pathway, led to EMT in colorectal cancer cells, which played a key role in the transition from inflammation to cancer. PLAC8 served as an independent risk factor for colorectal cancer prognosis.